Up and Down and Never Forward - Collins, Deborah (Homœopathic Links, 2014)
The case of a young man with a history of learning difficulties and emotional instability. His use of the words “up and down” for every aspect of his life led to a Lithium prescription, and his learning difficulties and his desire to spend all his time with his friends fine-tuned the prescription to Lithium phosphoricum. The remedy helped him to gain independence; he started saving money for the first time and learned to take responsibility for his life.
Keywords: Up and down; Impulsive; Friends; Fear alone; Attention Deficit Disorder; Lithium phosphoricum